Faktor Penentu Harga dalam Tinjauan Pemikiran Ekonomi Islam - Nurizal Ismail; Siti Aisyah; Devid Frastiawan Amir Sup (Islamic Economics Journal, 2020)
Price is one of the vital factors in economic studies, either at a micro or macro level. In general term, the concept of price can be found in primary (Al Qur’an and Sunnah) and secondary such as tafsir, fiqh, kalam, philosophy and history. Therefore, this study aims to find out the concept of price determinants developed by earlier Islamic economics scholars and compare it with the price theory in modern economics, which refers to Western economic thought. This study using a qualitative methodology using library research and content analysis. The results are the price determinant in the Islamic economy are according to the agreement of Islamic scholar based on demand and supply then shapes the price and volume of transactions. The other factors influencing the price mechanism are inventory, geography or places, consumption time, quality of goods, quantity and cost. The differences with the western economic view lie in the worldview aspect or the world view in understanding the price concept.